Reuni and University Expansion in UFMG from 2008 to 2012 - Edileusa Esteves Lima; Lucília Regina de Souza Machado (Universidade Federal do Rio Grande do Sul, 2016)
This article aims to analyse how well the goals of  Universidade Federal de Minas Gerais (UFMG) presented to the Ministry of Education (MEC) in 2008 for the Program of Support to Restructuration and Expansion Plans (Reuni) were achieved in 2012, as well as the changes that occurred in the institutional context as a result of the university expansion induced by this program. Documents related to the REUNI program were examined and the institutional data published by UFMG in its website and in its Annual Report from 2011 were analysed. The results of this research show that UFMG fulfilled almost entirely its proposals for new programs and expansion of vacancies. However, unexpected events and worsening of critical situations have arisen and require attention of university management.